Private Investment in Transport Increases in 2011, Focusing on the Road and Rail Sectors - Militaru, Andreea (World Bank, Washington, DC, 2014)
In 2011, 68 new transport projects reached financial or contractual closure in 15 lower-and upper-middle income countries: Argentina (1 project), Brazil (4), Chile (3),China (4), India (41), Kosovo(1), Mexico (3), Nigeria (1), Peru (3), Romania (1), the Russian Federation (1), South Africa (1), Sri Lanka (1), Togo (1), Turkey (2), and Zimbabwe (1). Total investment commitments in transport projects reached US$31.9 billion, of which US$30 billion were investments in new projects and US$1.9 billion were investments in existing projects. Total investment in transport projects in the region amounted to US$17 billion, a 4 percent increase from 2010 levels.